LIM Kinase 1 Mediates Estradiol Effects on the Phosphorylation of Cofilin1 in Eutopic Endometrial Stromal Cells During the Invasion and Proliferation of Endometriosis. (November 2019) - Liu, Jing; Zhang, Zhifang; Liu, Jiamei; Wang, Danbo
Endometriosis is an estrogen-dependent gynecological disease; however, the mechanism by which estradiol promotes the development of endometriosis, including invasion and proliferation, remains unclear. Estradiol is involved in cell invasion and proliferation by regulating the cytoskeleton. The abnormally high expression of cytoskeletal regulators (LIM kinase 1 [LIMK1] and cofilin1) is closely related to increased invasiveness and proliferation of eutopic endometrial stromal cells from endometriosis patients compared to normal eutopic endometrial cells. The aim of this study was to analyze the role of estradiol during invasion and proliferation through the LIMK1/cofilin1 pathway in the endometrium of women with endometriosis. To address this, primary eutopic endometrial stromal cells were isolated from the uteri of patients with endometriosis and cultured without estradiol. The phosphorylation of cofilin1 was analyzed by western blotting. Cell invasiveness and proliferation were evaluated following LIMK1 knockdown by RNA interference technology. We found that, before LIMK1silencing, the phosphorylation levels of cofilin1 and LIMK1 of eutopic endometrial stromal cells from endometriosis patients treated with estradiol were higher than cells not treated with estradiol ( P < .05 and P < .01, respectively). The total levels of cofilin1 and LIMK1 protein did not change ( P > .05 and P > .05, respectively). After LIMK1 silencing, the phosphorylation of cofilin1 by estradiol was significantly reduced, and invasiveness and proliferation were clearly and concurrently decreased ( P < .05 and P < .05, respectively). Thus, the phosphorylation of cofilin1 by estradiol is mediated by LIMK1, and estradiol is involved in regulating cell invasion and proliferation in endometriotic patients through the LIMK1/cofilin1 pathway.